2020
DOI: 10.3390/cancers12030668
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as an Adjuvant to Photodynamic Therapy in Resistant Basal Cell Carcinoma Cells

Abstract: Photodynamic Therapy (PDT) with methyl-aminolevulinate (MAL-PDT) is being used for the treatment of Basal Cell Carcinoma (BCC), although resistant cells may appear. Normal differentiated cells depend primarily on mitochondrial oxidative phosphorylation (OXPHOS) to generate energy, but cancer cells switch this metabolism to aerobic glycolysis (Warburg effect), influencing the response to therapies. We have analyzed the expression of metabolic markers (β-F1-ATPase/GAPDH (glyceraldehyde-3-phosphate dehydrogenase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
(70 reference statements)
0
19
1
1
Order By: Relevance
“…The reprogramming of mitochondrial metabolism is a common hallmark of cancer 10 . Cancer cells often switch metabolism from OXPHOS to aerobic glycolysis in order to produce energy, which can allow them to better adapt to the hypoxic tumor microenvironment and aid rapid proliferation 29 , 30 . The Warburg effect is associated with increased levels of glucose uptake and high rates of glycolysis, combined with the production of lactic acid, even in the presence of oxygen 11 .…”
Section: Role Of Mitochondrial Dysfunction In Cancer Developmentmentioning
confidence: 99%
“…The reprogramming of mitochondrial metabolism is a common hallmark of cancer 10 . Cancer cells often switch metabolism from OXPHOS to aerobic glycolysis in order to produce energy, which can allow them to better adapt to the hypoxic tumor microenvironment and aid rapid proliferation 29 , 30 . The Warburg effect is associated with increased levels of glucose uptake and high rates of glycolysis, combined with the production of lactic acid, even in the presence of oxygen 11 .…”
Section: Role Of Mitochondrial Dysfunction In Cancer Developmentmentioning
confidence: 99%
“…After irradiation, cells were incubated for 24 h in normal conditions before evaluation. This treatment conditions were selected according to previous works performed in our research group as capable to induce cell death in SCC13 and in A431 [ 10 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…PDT is a non-invasive and localized therapy that exerts minimal or no damage and improved healing capacity in the surrounding healthy tissues [ 10 , 11 ]. It consists of a two-step procedure by which the local or systemic administration of a photosensitizer (PS) or its precursor is followed by the irradiation of the lesion with light of a specific wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin as an Adjuvant to Photodynamic Therapy in Resistant Basal Cell Carcinoma Cells: Mascaraque et al showed evidence, in vitro and in vivo in mice, that metformin improves the cytotoxic effect of MAL-PDT either in PDT sensitive or resistant cells [ 12 ]. This effect was not related with an increase in PpIX accumulation but related to the activation of pAMPK and the suppression of the mTOR pathway.…”
Section: Research Snippetsmentioning
confidence: 99%